2009
DOI: 10.1007/s00415-009-5243-y
|View full text |Cite
|
Sign up to set email alerts
|

Formation and development of Lewy pathology: a critical update

Abstract: Filamentous protein inclusions in neurons (Lewy bodies, LB) and dystrophic neurites containing pathologic alpha-synuclein (alpha Syn) are the morphologic hallmarks of sporadic Parkinson disease (PD) and dementia with Lewy bodies (DLB), but are also found in aged subjects and in a variety of neurogenerative disorders. They occur in the central, peripheral, and autonomic nervous system as an essential or coincident feature. Their formation runs through several phases from initial dust-like particles cross-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
148
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 92 publications
2
148
0
10
Order By: Relevance
“…Prions are composed solely of PrP Thus, the propagation of AS lesions by cellto-cell passage appears to be similar as that in other neurodegenerative disorders (see [9,626] [429][430][431]636]. The formation of axonal AS deposits and "pale bodies" [637] preceds the development of LBs in affected neurons.…”
Section: Lbs In Transplanted Daergic Neurons Has Beenmentioning
confidence: 74%
See 1 more Smart Citation
“…Prions are composed solely of PrP Thus, the propagation of AS lesions by cellto-cell passage appears to be similar as that in other neurodegenerative disorders (see [9,626] [429][430][431]636]. The formation of axonal AS deposits and "pale bodies" [637] preceds the development of LBs in affected neurons.…”
Section: Lbs In Transplanted Daergic Neurons Has Beenmentioning
confidence: 74%
“…Despite many similarities between DLB and PDD, several morphological differences have been demonstrated, in particular higher amyloid plaque load in striatum, usually absent in non-demented PD [37,38,630,708], and more severe AS load in hippocampal CA2/3 areas [429][430][431]. A recent study showed DLB cases having more severe Aβ load than PDD, but no differences in neuritic Braak and AS scores, while others found higher Aβ scores in cortical and subcortical areas [692].…”
Section: Relationship Between α-Synuclein and Lewy Pathologymentioning
confidence: 99%
“…Although intracellular protein accumulation and aggregation are characteristics of many different neurological disorders the relationship between protein aggregates accumulation and pathogenesis has not been defined yet [39][40][41][42][43][44]. Indeed protein inclusions have been suggested to be toxic, protective or simply correlate with the disease without influencing its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, morphologic hallmarks of sporadic PD (Lewy bodies and dystrophic neurites containing pathologic α-synuclein) may appear initially in the lower brainstem [2]. However, Lewy pathology can correlate poorly with neuronal loss in specific areas, thus its validity in predicting neuronal disintegration is questionable [29]. In fact, noradrenergic neurons in the LC are relatively preserved in early PD and do not exhibit the same intracellular changes as in the substantia nigra [30].…”
Section: In Vivo Versus Anatomopathological Studiesmentioning
confidence: 99%